Payment Risk Estimation in the Markets of Lithuania, Latvia and Estonia - Grigonytė, Ingrida; Sūdžius, Vytautas (Business, Management and Economics Engineering, 2010)
According to difficult business situation, payments to business partners, clients or suppliers are delayed more than usual. That could be a serious threat to enterprises. In this article solvency importance to all business units as well as company‘s ability to pay their debts to other market units (partners, suppliers, etc.) in Lithuania, Latvia and Estonia are discussed. The data used in this article are taken from Intrum Justitia OY EPI (European Payment Index) research. Payment index in three Baltic region countries, harm that can be done to enterprises, and company‘s behaviour according to payment delays are analysed. At the end of the article there are recommendations of actions needed to be taken in order to prevent company‘s solvency.Article in Lithuanian.Mokėjimų rizikos įvertinimas Lietuvos, Latvijos ir Estijos rinkose